Depletion of Mageb16 induces differentiation of pluripotent stem cells predominantly into mesodermal derivatives. Issue 1 (December 2017) - Gaspar, John; Srinivasan, Sureshkumar; Sureshkumar, Poornima; Doss, Michael; Hescheler, Jürgen; Papadopoulos, Symeon; Sachinidis, Agapios
Abstract The Melanoma-associated Antigen gene family (MAGE) generally encodes for tumour antigens. We had identified that one of the MAGE gene members, Mageb16 was highly expressed in undifferentiated murine embryonic stem cells (ESCs). While the role of Mageb16 in stemness and differentiation of pluripotent stem cells is completely unknown, here, in our current study, we have demonstrated that Mageb16 (41 kDa) is distributed in cytosol and/or in surface membrane in undifferentiated ESCs. A transcriptome study performed at differentiated short hairpin RNA (shRNA)-mediated Mageb16 knockdown (KD) ESCs and scrambled control (SCR) ESCs until a period of 22 days, revealed that Mageb16 KD ESCs mainly differentiated towards cells expressing mesodermal and cardiovascular lineage - gene markers. Gene markers of other mesoderm-oriented biological processes such as adipogenesis, osteogenesis, limb morphogenesis and spermatogenesis were also significantly enriched in the differentiated Mageb16 KD ESCs. The expression levels of contractile genes were higher in differentiated Mageb16 KD ESCs when compared to differentiated SCR and wild ESCs, suggesting a higher cardiomyogenic potential of Mageb16 depleted ESCs. Further analysis indicates that regulative epigenetic networks and nucleocytoplasmic modifications induced by the depletion of Mageb16, may play a probable role in differentiation.